Pengaruh Metode Belajar Matematika Asik (BELMASIK) terhadap Hasil Belajar Siswa pada Materi Komposisi dan Invers Fungsi - Vioni, Ria Octa; Yohanie, Dian Devita; Widodo, Suryo; Handayani , Aprilia Dwi (Universitas Nusantara PGRI Kediri, 2022)
Abstract T The material of composition and invers function is one of the materials that require students’ active in the learning process to increase the students’ comprehension. The purpose of this research is to find out the influence of the implementation of BELMASIK learning method on the students’ achievement in composition and invers function. The research approach was quantitative using Pre-Experimental Design that was One-Group Pre-test-Post-test. 39 students of the-tenth grade of OTKP 1, OTKP 2, OTKP 3 at Vocational High School PGRI 2 Kediri was choosen as sample. Treatment was conducted three meetings. The results of this research showed that there was improvement on the students’ achievement in composition and invers function. It can be seen that the averages of the pre-test score was 57,5385 (SD ) become 72,0513 (SD ) with the Sig. (2-tailed) value was . It means that the BELMASIK learning method was affected the students’ achievement. This research proved that the BELMASIK method could be applied in teaching composition and invers function materials to increase students’ achievement.